Comparison between side-lying and standing positions for hip abductor strength assessment - de Castro M.P.* (2022)
© 2022 Elsevier LtdBackground: The hip abductor muscles control the pelvis in the frontal plane and allow the maintenance of trunk position and dynamic balance during weight-bearing activities. Objective: To compare the side-lying and standing positions for hip abductor strength assessment with regards to torque production and myolectric activity. Method: Concentric and eccentric hip abductor peak torque and total work, and myoelectric activity of the tensor fascia lata, gluteus medius, and inferior and superior portions of the gluteus maximus muscles were measured during maximal isokinetic tests for hip abductor strength in the side-lying and standing positions. The Wilcoxon test was used to compare variables between the positions. Results: Peak torque values did not differ between side-lying and standing positions for both concentric and eccentric contraction modes (p > .05). During standing position, greater concentric total work was observed (p = .013). This position resulted in a lower activity of the tensor fascia lata muscle (p = .005) compared to side lying position. Myoelectric activity of gluteus medius, and inferior and superior portions of the gluteus maximus was similar between positions (p > .05). Conclusion: Both positions presented similar peak torque values and, during the standing position, a greater concentric total work and lesser activation of the tensor fascia lata was observed. Standing position can be used when emphasis on the superior portion of gluteus maximus over the tensor fascia lata is intended.